Antibacterial activity of benzoyl and halobenzoyl thiourea bearing α- and β-alanine - Ibrahim, Maizatul Akma; Husin, Atiyah; Ngah, Nurziana; Zakaria, Nor Hafizah (Zibeline International Publishing, 2021)
Antibacterial activity of synthetically synthesized benzoyl thiourea and halobenzoyl thiourea bearing α-alanine and β-alanine compounds were investigated against gram-positive bacteria (Staphylococcus aureus and Bacillus subtilis) and gram-negative bacteria (Esherichia coli). The study of antibacterial activity of the compounds was conducted by using the disc diffusion method and minimal inhibitory concentration (MIC) as well as minimal bactericidal concentration (MBC). The results indicate that 4-fluorobenzoylthiourea α-alanine, benzoylthiourea α-alanine, 4-fluorobenzoylthiourea β-alanine, 4-chlorobenzoylthiourea β-alanine, 4-bromobenzoylthiourea β-alanine, and benzoylthiourea β-alanine possess weak to strong antibacterial activity on all of tested bacteria. The strongest antibacterial activity was found in the 4-fluorobenzoylthiourea α-alanine, whereas the weakest antibacterial activity was exhibited in 4-fluorobenzoylthiourea β-alanine. S. aureus was found the most susceptible toward these thiourea derivatives, indicating bactericidal activity against the bacteria.